(untitled) (In situ, 2024)
In 2023, students and professors of the Department of Archaeology and the Department of Art History of the University of Zadar experimentally restored a prehistoric tumulus on Biokovo mountain at the Lokva site. The reconstruction incuded processes, techniques and tools used to build the mound, which had a perimeter ring raised to the height of four rows of stone, an embankment of coarse stone, gravel and earth, and two reconstructed medieval graves with massive lids.